Dual-functioning Targeted ADAM17 Blocker CD16 (TAB16) mediates selective ADAM17 inhibition in NK cells and engages overexpressed ADAM17 in tumor cells to induce cytotoxicity - Dixon, Kate J.; Hullsiek, Robert; Wang, Sam; Friess, Ryan R.; Matson, Anders W.; Soignier, Yvette; Lenvik, Alexander J.; Wu, Jianming; Hart, Geoffrey T.; Felices, Martin; Walcheck, Bruce (Frontiers in Immunology, 2026)
IntroductionNatural killer (NK) cells are innate lymphocytes that kill tumor cells by natural cytotoxicity and antibody-dependent cell-mediated cytotoxicity (ADCC). Human NK cells mediate the latter process exclusively by the IgG Fc receptor CD16 (FcγRIIIA). Cell surface levels of this activating receptor are tightly regulated by the metalloprotease ADAM17, which cleaves CD16 upon NK cell activation or cellular stress. We have reported that Medi-1, a fully human IgG1 mAb, blocks ADAM17, and its Fc region is simultaneously engaged by CD16, inducing and prolonging its signaling, which synergizes with cytokine stimulation, such as IL-15. To exploit these distinctive features of Medi-1 while also addressing limitations of the mAb, such as the varied affinity by which CD16 binds to it due to receptor polymorphisms and the risk of broadly blocking ADAM17 activity, we engineered Targeted ADAM17 Blocker CD16 (TAB16).MethodsTAB16 was generated with a camelid heavy-chain variable domain specific to CD16 linked to a single-chain variable fragment derived from Medi-1. TAB16 was further modified by the linkage of an IL-15 moiety to generate TAB16/15. Primary human NK cells were treated with TAB16 or TAB16/15 and evaluated for proliferation by cell dilution dye, ADAM17 blocking, activation marker expression, and cytotoxicity against ovarian cancer cell lines in real-time by IncuCyte assays. ResultsThe TAB16 bispecific engager targeted NK cells and blocked ADAM17. A novel feature of TAB16 is its dual functionality, as it synergizes with IL-15 to enhance NK cell activation and proliferation and targets ADAM17 overexpressed on cancer cells to induce ADCC. TAB16 is a modifiable backbone to which additional functional components can be added, such as IL-15 (TAB16/15) for consolidated and multifaceted activity.DiscussionOur ADAM17-engaging platform offers a unique approach for targeted ADAM17 inhibition to augment the anti-tumor function of endogenous and therapeutic NK cells.